Pengaruh Perputaran Modal Kerja dan Perputaran Persediaan Terhadap Profitabilitas Perusahaan Properti dan Real Estate yang Terdaftar di Bursa Efek Indonesia - Meidita Kurnia; Hendra Gunawan (Pusat P2M Politeknik Negeri Batam, 2021)
This study aims to test whether working capital turnover has a negative effect on profitability and inventory turnover has a positive effect on the profitability of property and real estate sector companies listed on the IDX for the 2014-2018 period. This study has one dependent variable, namely profitability and five independent variables, namely working capital turnover, inventory turnover, asset turnover, short-term bank loans, liquidity and mark up. The sampling method used the cross-sectional technique, with a sample of 210 companies in the 5 years of the study. The results of the study found that working capital turnover has a negative effect and inventory turnover has a positive effect, asset turnover has a positive effect, short-term bank loans have a negative effect, while liquidity and mark-up have a negative effect on company profitability. This shows that the lower the working capital turnover of a company, the lower the company's profitability, the smaller the inventory turnover rate, the higher the company's profitability, the higher the asset turnover, the better the company's ability to generate profits, the higher the company's short-term debt. the lower the company's profitability, the higher the liquidity and mark-up, the more difficult the company's ability to generate high profits.